Interação da matéria de vórtices com estruturas de defeitos : detecção das primeiras penetrações - Zadorosny, Rafael (Universidade Federal de São Carlos, 2009)
This thesis results from a systematic study of the interactions between penetrated vortices and pinning centers carried out on structured superconductors films of YBCO, Nb and Pb. A regular array of pinning centers (antidots, ADs) was inserted in those samples by mechanical indentations (in YBCO and Nb films), and by a lithographic processes (Pb). The structure of the YBCO film counts with 1680 ADs, each with an effective diameter of 2 μm, distributed in a square array of 50 μm size. The Nb film has 900 ADs, with an effective diameter of 1 μm, forming a square array of 10 μm size. The Pb film has more than 3.7 millions of square ADs, with 0.8 μm of lateral dimensions, and the formed array has size of 1.5 μm. Those systems were studied by DC and AC magnetometry. As the Commensurability Field (Matching Field, MF) associated with their structures, is very small, it was not possible to study the commensurability effects in YBCO and Nb films. However, the Pb film has a structure which MF is 9.1 Oe, so that, jumps in its magnetic response could be observed each time that the applied field reached an integer multiple of that field. The YBCO film was studied in very small DC fields, i.e., only in the presence of the Earth magnetic field. We verified that, as the vortices penetrate the sample, they arrange themselves into the ADs in such a way that the sample behave as a collection of small superconductors arranged side by side. This study was not carried out on the other samples because the preparation of this experiment is very difficult and needs special experimental conditions which are rarely available in our laboratory. Particularly, for the Pb film, we could not have enough time to prepare the experiment due to its rapid degradation. We have studied the temperature dependence of the remnant magnetization (thermoremanence) of the Pb film for several cooling fields. That study revealed that the remnant response of the system increases with the cooling field, however, a saturation value is reached for fields greater than the first MF of its array. This behavior is due to the proximity of the ADs which hinders the pinning of vortices in interstitial regions. The remanence rises sharply up to the first MF, when the remnant flux counts one quantum per AD. For greater fields, the remnant rising rate has a sudden change and approaches to zero. In measurements of χAC as a function of the excitation field amplitude, all of the studied samples revealed that, in the beginning of the penetration, the vortices are impeded to move by the first front of ADs. Upon reaching a certain number, vortices eventually cross this first barrier and move deeper into the sample, up to the second front. In other words, at low temperatures and vortex densities (or, equivalently, at low AC fields), the penetration takes place layer by layer, i.e., the AD fronts act as contention barriers for the entrance of vortices, and they have to be suppressed one by one. We have studied the temperature dependence of the remnant magnetization (thermoremanence) of the Pb film for several cooling fields. That study revealed that the remnant response of the system increases with the cooling field, however, a saturation value is reached for fields greater than the first MF of its array. This behavior is due to the proximity of the ADs which hinders the pinning of vortices in interstitial regions. The remanence rises sharply up to the first MF, when the remnant flux counts one quantum per AD. For greater fields, the remnant rising rate has a sudden change and approaches to zero. In measurements of χAC as a function of the excitation field amplitude, all of the studied samples revealed that, in the beginning of the penetration, the vortices are impeded to move by the first front of ADs. Upon reaching a certain number, vortices eventually cross this first barrier and move deeper into the sample, up to the second front. In other words, at low temperatures and vortex densities (or, equivalently, at low AC fields), the penetration takes place layer by layer, i.e., the AD fronts act as contention barriers for the entrance of vortices, and they have to be suppressed one by one.
Keywords: Supercondutores; Matéria de vórtices; Defeitos colunares; Filmes finos; CIENCIAS EXATAS E DA TERRA::FISICA